Evaluating the Impact of Digital Collaboration Tools on Remote Work Well-Being and Productivity - Sláma, Jan (2024)
This master’s thesis investigates the impact of digitalization adoption on employee well-being in remote working environments within ICT organizations based in Prague, Czechia. The study evaluates the effectiveness of digital platforms, namely virtual collaboration spaces (VCS), enhanced communication channels (ECC), and project management software (PMS), in the promotion of well-being outcomes. A quantitative research approach is utilized, and data is collected from employees via an online questionnaire, analyzing the relationship between digital platform intensity of usage and indicators of well-being. Research supports that higher intensity of VCS usage is positively associated with a greater sense of team cohesion (r = 0.616) and employee satisfaction (r = 0.624). Higher intensity of ECC usage is associated with better work-life balance (r = 0.291) and reduced feelings of isolation (r = 0.341). However, only 8.5% and 11.6%, respectively, of the variability in these indicators are explained by the intensity of usage of ECC. PMS intensity of usage has the highest positive correlation with the digitalization impact on remote workers' well-being (r = 0.707), followed by VCS usage (r = 0.633) and ECC usage (r = 0.429).